DIDA DAN KADA DALAM BAHASA, AGAMA, SERTA KERAGAMAN BUDAYA - Roikhan Muhammad Aziz (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
Cultural diversity provides insight for expansion in Indonesian Language. It is analogous to the phenomenon of religious language which continue to search for universal values of culture and existing knowledge. Cultural language insists on diversity for grace, while thrusting religious language universality which became the foundation for the various culture.Indonesian Language will be the bridge for the universality and diversity over the faculty of language and literature education. It requires the completion of Indonesian Grammatical Structure to be more compatible with the universality of religion language including the adjustment of personal pronouns as numbered one, two, and at least three persons.In Arabic Grammatical Structure, Nahwu and Shorof, person pronoun consists of single, twin, and plural. While in Indonesian Grammatical Structure only recognize personal pronoun as singular and plural. In this study of grammatical structures are using a qualitative approach refers to the Hahslm method based on methodology of Sinlammim. This methodology is based on the Islam which is the foundation of Al-Quran highlights Sura Ali Imran [3]: 19 and Al -Hijr [15]: 87. Required a nonlinear thinking to combine the comparative analysis, analogy, and notification in religion and diversity of knowledge.Personal pronoun of the 2nd and 3rd need to be inserted in the form of a personal pronoun which amounts of two so that the pronoun which amounts of many as a personal pronoun at least three people. With inserted pronouns 2nd person namely Kada or You Both and pronouns 3rd person namely Dida or He/She Both, then the Indonesian have found a more universal grammar and reflect diversity. Thus meaning 'many' in religion can be agreed upon as 'something that amounts to at least three', It will be contributing a new grammar in search of knowledge core and cultural diversity.